Manajemen Program Ujian Tahfidz dan Tahsin Al-Quran Juz 30 di Ma’had Al-Jami’ah sebagai Persyaratan Munaqosyah Mahasiswa UIN STS Jambi - Agung Gumelar (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to determine the management of the tahfidz and tahsin Quran juz 30 exams at Ma'had Al-Jami'ah UIN STS Jambi. This research uses descriptive qualitative research methods. Data collection uses interview, observation, and documentation methods. The results of this study show that the management process of the tahfidz and tahsin Quran exams at Ma'had Al-Jami'ah UIN STS Jambi has carried out management functions, namely planning, organizing, implementing and evaluating. The planning of the tahfidz and tahsin Quran programs is carried out through the determination of targets, goal setting, method determination, method determination, and strategy determination. The implementation of the tahfidz and tahsin Quran programs has proceeded in accordance with the activity plans that are prepared in a structured and systematic manner. The control of the tahfidz and tahsin Quran programs has been carried out through activities to build cooperative relationships between supervisors and tutors, mentors in motivating tutors, mentors in fostering and directing tutors, and mentors in establishing communication with tutors.